Influence of NCM Particle Cracking on Kinetics of Lithium-Ion Batteries with Liquid or Solid Electrolyte. Issue 10 (17th June 2020) - Ruess, Raffael; Schweidler, Simon; Hemmelmann, Hendrik; Conforto, Gioele; Bielefeld, Anja; Weber, Dominik A.; Sann, Joachim; Elm, Matthias T.; Janek, Jürgen
Abstract : In liquid electrolyte-type lithium-ion batteries, Nickel-rich NCM (Li1+ x (Ni1− y − z Co y Mnz )1− x O2 ) as cathode active material allows for high discharge capacities and good material utilization, while solid-state batteries perform worse despite the past efforts in improving solid electrolyte conductivity and stability. In this work, we identify major reasons for this discrepancy by investigating the lithium transport kinetics in NCM-811 as typical Ni-rich material. During the first charge of battery half-cells, cracks form and are filled by the liquid electrolyte distributing inside the secondary particles of NCM. This drastically improves both the lithium chemical diffusion and charge transfer kinetics by increasing the electrochemically active surface area and reducing the effective particle size. Solid-state batteries are not affected by these cracks because of the mechanical rigidity of solid electrolytes. Hence, secondary particle cracking improves the initial charge and discharge kinetics of NCM in liquid electrolytes, while it degrades the corresponding kinetics in solid electrolytes. Accounting for these kinetic limitations by combining galvanostatic and potentiostatic discharge, we show that Coulombic efficiencies of about 89% at discharge capacities of about 173 mAh gNCM −1 can be reached in solid-state battery half-cells with LiNi0.8 Co0.1 Mn0.1 O2 as cathode active material and Li6 PS5 Cl as solid electrolyte.